Germline and somatic mutations of MSH6 and MSH3 genes behind MSH2 deficient colorectal cancer in Lynch syndrome - Olkinuora, Alisa (My University, 2019)
Colorectal cancer (CRC) is the third most common type of cancer globally. About 25% of CRC cases appear in familial clusters, of which at least 5% are caused by inherited factors. Lynch syndrome is the most common CRC syndrome, with the average age of onset less than 50 years of age. Apart from CRC, endometrial and cervical cancers are very common in Lynch syndrome. Lynch syndrome is characterized by pathogenic mutations in mismatch repair (MMR) genes; MLH1, MSH2, MSH6, and PMS2. Mismatch repair is a post-replicative DNA repair mechanism which targets mismatches. Globally, MSH2 mutations are most common, though in Finland, 70% of the Lynch cases are caused by a mutation in MLH1. There are roughly 270 Lynch syndrome families in Finland. The material for this thesis consists of 60 blood- and normal mucosa FFPE (Formalin-Fixed Paraffin-Embedded) samples, as well as three tumour samples from three patients. The samples used in this thesis belong to patients with a medical history akin to Lynch syndrome patients, although no cancer predisposing mutation has been found. The samples are analysed with MS-MLPA (Methylation-Specific Multiplex Ligation-dependent Probe Amplification), MLPA (Multiplex Ligation-dependent Probe Amplification), and deep sequencing techniques (whole genome sequencing, targeted deep sequencing). The aim is to find known pathogenic mutations and to find out what triggered tumorigenesis, as well as to recognise new causative mutations for Lynch syndrome. Atypical of Lynch syndrome, three of the studied patients were found to have a truncating germline mutation in MSH6 although the tumour phenotypes suggested the causative mutation to be in MSH2. The truncating MSH6 mutation likely caused MSI which targeted MSH3, inactivating the gene in some of the cells in the colorectum. The inactivation of both MSH6 and MSH3 means that MSH2 protein has no binding partners and will likely be degraded in tumour tissue. The truncated MSH6 protein may also be able to dimerize with MSH2 but lack any DNA repair activity. This may result in the degradation of the MSH2-MSH6 complex or the faulty complex may compete with wild type MSH2-MSH6, causing microsatellite instability.
Keywords: Lynch syndrome, DNA Mismatch Repair, Colorectal Neoplasms, Whole Genome Sequencing, Methylation, Mutation